1991
DOI: 10.3109/00016349109006193
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laparoscopic electrocoagulation in infertile patients with minimal or mild endometriosis

Abstract: The cumulative pregnancy rates in 17 infertile patients with minimal or mild endometriosis who underwent laparoscopic electrocoagulation were compared with those of 20 similar patients who underwent only diagnostic laparoscopy. A life-table method of analysis was used. No significant differences in pregnancy rates was evident at either 6 months (p greater than 0.5) or 12 months (p greater than 0.5) of follow-up. These results question the use of laparoscopic electrocoagulation for the treatment of infertile pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…The hypothesis that surgical removal of minimal to mild endometriosis improves fecundity has been confirmed by some (4,5) but not by all (6,7) investigators in mostly retrospective controlled studies. Recently, in a randomized, controlled Canadian trial, the hypothesis was confirmed that laparoscopic resection or ablation of minimal to mild endometriosis and associated adhesions enhances fecundity (8).…”
mentioning
confidence: 90%
“…The hypothesis that surgical removal of minimal to mild endometriosis improves fecundity has been confirmed by some (4,5) but not by all (6,7) investigators in mostly retrospective controlled studies. Recently, in a randomized, controlled Canadian trial, the hypothesis was confirmed that laparoscopic resection or ablation of minimal to mild endometriosis and associated adhesions enhances fecundity (8).…”
mentioning
confidence: 90%
“…Thus, the suggested endocrinologically related pathogenesis of endometriosis and myomas (8) cannot be sustained by our data, at least in EAI. Although in some studies poor sperm characteristics (9) or function (10) have been described studying selected populations, in our infertile couples sperm characteristics were similar in EAI and NEI, or even somewhat better in EAI. This probably reflects a similar frequency of subfertility in both populations.…”
Section: Discussionmentioning
confidence: 73%
“…Dahlberg (17) reported on the presence of asymptomatic bacteriospermia in male partners of patients with endometriosis, and Mahmood et al (18) and Waller et al (19) speculated on the possible association between male infertility and the development of endometriosis in the female. Arumugam (20) reported on sperm dysfunction in partners of infertile patients with minimal or mild endometriosis, using sperm penetration testing with bovine cervical mucus.…”
Section: Discussionmentioning
confidence: 99%